A new species from the genus Astochia Becker, 1913 (Diptera: Asilidae) from the Sundarban, India with an updated checklist of Indian species. (2nd April 2020) - Roy, Sankarsan; Parui, Panchanan; Mitra, Bulganin; Chakraborty, Susanta Kumar
ABSTRACT: A new asilid species Astochia venkataramani sp. nov. is described with supportive illustrations of male genitalia and body parts, from Sundarban Biosphere Reserve, West Bengal, India. An updated checklist of the Indian species of Astochia Becker is also included. The holotype specimen of the new species has been deposited in the National Zoological Collections of Zoological Survey of India, Kolkata. An updated identification key to the species of Astochia from West Bengal is also provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D36A20CC-9D56-4050-912E-2E846D5F6E91